Linking User-Perception Diversity on Ecosystems Services to the Inception of Coastal Governance Regime Transformation - Herbst, Dannieli F.; Gerhardinger, Leopoldo Cavaleri; Hanazaki, Natalia (Frontiers in Marine Science, 2020)
In this paper we explore the challenges for transforming a wide and fragmented coastal governance system towards an ecosystem-based regime by translating shared values of nature into radically novel territorial development policies at highly disputed seascapes. We report an official coastal management institutional experiment in South Brazil, where the way direct ecosystem users (fishers, miners, mariculture, tourism and leisure, aquatic transport agents and researchers) perceive and classify ecosystem services was assessed during 19 collaborative sectoral workshops held with 178 participants from six coastal cities surrounding Babitonga Bay estuarine and coastal ecosystems (Santa Catarina state, South Brazil). Participants collectively enlisted the benefits, rights and resources (or services) they obtain from these ecosystems, rendering a total of 285 citations coded to conventional ecosystem services scientific typologies (127 ecosystem services grouped in 5 types and 31 subtypes). We explore patterns in ecosystem services classificatory profiles, highlighting ecosystem user’s salient identities and exploring how they shape political actions in relation to an ecosystem-based normative perspective. Food (provisioning service) and tourism and leisure (cultural service) are perceived by all user groups, and hence consist of a core set of perceived shared value amongst direct ecosystem users to inform future transformation narratives. Differences in perception of values amongst user groups combined with high levels of power asymmetry and fragmentation in decision-making, are steering the analyzed system towards an unsustainable social-ecological pathway. The governance regime has been largely favoring subsets of services and unfair distribution of benefits, disregarding a more diverse array of real economic interests and potential ecological knowledge contributions. Our integrative and deliberative ecosystem services valuation approach advances understanding of critical features of the scoping phase of ecosystem services assessment initiatives in the coastal zone. We therefore provide empirically grounded and theoretically informed suggestions for the promotion of local knowledge integration through combination of methods that supports transformational research agendas. We ultimately hope to have established new groundwork to fulfilling alternative visions for the regional social-ecological system transformation to a more socially and ecologically coherent and equitable development trajectory.